2015
DOI: 10.18388/abp.2015_1127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of uropathogenic Escherichia coli biofilm formation under different growth conditions

Abstract: The ability to form different types of biofilm enables bacteria to survive in a harsh or toxic environment. Different structures of biofilms are related to different surfaces and environment of bacterial growth. The aim of this study was analysis of the biofilm formation of 115 clinical uropathogenic Escherichia coli strains under different growth conditions: surface for biofilm formation, medium composition and time of incubation. The biofilm formation after 24 h, 48 h, 72 h and 96 h was determined spectropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…Five clinical Escherichia coli strains isolated from the urine of patients suffering from urinary tract infection were selected for this study. They belong to the characterized bacterial collection used in previous studies [30,32,33]. The basic criteria for their selection were the sensitivity to all analyzed antibiotics and the varied occurrence of virulence factor genes.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five clinical Escherichia coli strains isolated from the urine of patients suffering from urinary tract infection were selected for this study. They belong to the characterized bacterial collection used in previous studies [30,32,33]. The basic criteria for their selection were the sensitivity to all analyzed antibiotics and the varied occurrence of virulence factor genes.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…The biofilm formation assay was carried out by 0.3% crystal violet staining according to the protocol described previously [32]. The bacteria were grown in triplicate on the 96-well plates at 37°C in the LB broth.…”
Section: Biofilm Formation Assaymentioning
confidence: 99%
“…The decrease of the P. mirabilis growth rate might inhibit the biofilm formation, unlike in E. coli . We also observed that the biofilm formation on the glass correlated proportionally with that on the polyurethane, which was again in contrast to E. coli [46]. Czerwonka et al [11] reported that high hydrophobicity of the P. mirabilis cell surface correlated with low biofilm amount, which is important for hydrophobic surfaces like glass.…”
Section: Discussionmentioning
confidence: 79%
“…The ability to form biofilm varies remarkably, even among strains of the same species [4345]. Our results (Fig 7) indicate that the P. mirabilis biofilm may be stronger than that of E. coli [46]. That may mean that P. mirabilis grows faster, providing greater biofilm yield, which might be important during the host invasion.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation